HOPELESS TO HOPEFUL: a clinical study on management of periodontal abscess with grade II furcation involvement – endodontic and periodontal interdisciplinary approach: case report - Chandrashekar, K. T.; Saxena, Chhavi (Archives of Oral Research, 2010)
OBJECTIVES: To present a case report of management of grade II furcation involvement associatedwith a periodontal abscess of mandibular right first molar utilizing an alloplastic bone graft. DISCUSSION:The case was diagnosed as periodontal abscess with grade-II furcation involvement and was primaryperiodontal lesion with secondary endodontic involvement. Treatment included scaling, root planing &curettage and root canal treatment of the involved tooth. Periodontal flap surgery was done with bonegraft placement in the furcation area. RESULTS: Patient was evaluated after onear. Radiographicexamination showed healing of furcation defect as well as resolution of periapical inflammation. Clinicalevaluation revealed resolution of furcation involvement as well as reduction of tooth mobility.